APPLICATION OF HOROWITZ’S THEORY OF TRAUMA THERAPY TO LITERARY STUDIES - TAKING THREE CHARACTERS IN KUNDERA’S NOVELS AS CASES - Amalia Qistina Castaneda Abdullah; Qian Zhao (Journal of Islamic, Social, Economics and Development, 2024)
Using Horowitz’s theory of trauma therapy to analyse the trauma treatment of three victims in Milan Kundera’s novels who suffered trauma, the article aims to explore the value of Horowitz’s theory to literary criticism research. The following three points are the research findings based on case study. Firstly, Horowitz’s trauma theory has important guiding significance for studying literary works. Secondly, studying literary works can promote the development of Horowitz’s trauma theory. Finally, research on trauma psychology provides the possibility for the fusion of medicine and literature studies.